Making Sense of the Shift in Paradigm on Cartel Enforcement: The Case for Applying a Desert Perspective - Quaid, Jennifer (McGill Law Journal / Revue de droit de McGill, 2012)
Soon after the coming into force of changes to the criminal provisions in the Competition Act, the commissioner of competition signalled that cartel enforcement would start to reflect a new mindset, one that treats cartels as truly criminal. But while the impetus for this shift in paradigm is well-intentioned—to give effect to a stronger criminal law mandate following the amendments—it is poorly explained, because its defenders continue to refer to the predominant deterrence rationale used in competition law, even though applying a harm-based view of crime and punishment to cartels fails to explain why criminal enforcement is needed.I believe that applying a desert perspective offers a compelling alternative explanation for this shift toward treating cartels as truly criminal. Drawing on the work of Arthur Ripstein, I offer an account of cartel enforcement that focuses on the inherently wrongful disregard for competition that characterizes cartels. I argue that seeing cartels as a particularly serious misuse of the competitive system, one that is so fundamentally at odds with the notion of a competitive marketplace that it cannot be tolerated, is what justifies recourse to the consistent and uniquely public response of the criminal law. Seen in this light, bringing a more criminal law-oriented mindset to bear on cartel enforcement makes sense in way that this shift in paradigm does not when justified in deterrence terms.